Influencia de dos tipos de raciones en estado natural y comercial, en el crecimiento de juveniles de Colossoma macropomum (gamitana), criados en jaulas flotantes, en el Instituto de Investigaciones de la Amazonía Peruana (IIAP) Iquitos-Perú - Falcón García, Mayrita Steffi (2023)
The present study was carried out at the facilities of the Instituto de Investigaciones de la Amazonía Peruana (IIAP), Carretera Iquitos Nauta km. 4.5, province of Maynas, department of Loreto, between the months of December 2018 to March 2019. The objective was to determine the influence of two types of rations in a natural state (chicken viscera T1) and commercial (balanced food T2) on the growth of juveniles of Colossoma macropomum, gamitana. Using a total of 24 juveniles with an initial weight and length of 161.4 ± 20.5 g and 22.3 ± 1.3 cm respectively, distributed in 8 cages, at a density of 3 fish per cage (m3), for 90 days. The fish were fed with two experimental rations, raw chicken entrails (T1= 19.23% CP) and balanced food (T2= 30% CP). The treatment that obtained the greater growth in length, weight, better zootechnical indices, higher values of viscerosomatic and hepatosomatic body indices and better results in fillet yield with and without skin was T2, the physical and chemical parameters of the water were within the optimal range for the cultivation of the species. The organoleptic characteristics of raw and cooked fish showed a difference in body shape, color, smell, flavor, juiciness and texture between both portions, presenting greater acceptance in T2; Finally, in the bromatological analysis of the fish muscle, the fish from T1 had a higher percentage of moisture, and the fish from T2 had a higher amount of lipids. In conclusion, the rations used influenced the juveniles of Colossoma macropomum, gamitana.